Released from foreign detention: Examining reoffending rates among returning Dutch detainees in the Netherlands - Van Hall, Matthias (European journal of probation, 2021)
At least 1,900 Dutch detainees are detained abroad yearly. They are housed in foreign detention because they are accused of having committed a criminal offence in a country that is not their country of residence. This study used data regarding Dutch detainees who were supervised by the International Office of the Dutch Probation Service to examine detainees’ background characteristics and their offending behaviour after returning to the Netherlands. The findings show that 23% of the Dutch detainees reoffended within 2 years of release from foreign detention. Furthermore, several background characteristics, such as their age at release from foreign detention, are related to reoffending behaviour.